LutzoDex™—A digital key for Brazilian sand flies (Diptera, Phlebotominae) within an Android App - de Almeida Rocha, Douglas; de Almeida, Maxwell Ramos; de Sena Batista, Jainaine Abrantes; de Andrade, Andrey José (Zootaxa, 2019)
Here we present an Android mobile application (app) for the identification of Brazilian phlebotomine sand fly species. The app, which is named LutzoDex™, relies on information included in a data source with morphological and morphometrical characters. This tool can present up to seven answer options to a question. Images of morphological structures can be referenced to make identification easier, and users can see a list of possible species based on the features they report. Maps are also used to determine the geographical distribution and whether the species is incriminated or suspected as a vector of Leishmania spp. in Brazil. The app is available free of charge in both English and Portuguese in the Google Play Store at https://play.google.com/store/apps/details?id=max.com.lutzodex&hl=pt_BR.